Structural Class I viroporin characteristics displayed by p33. - Vicken Aknadibossian (22676694) (2025)
A) The TMD of p33 compared with that of three known viroporins (IAV M2, HIV-1 Vpu, and SARS-CoV E) representing the underlined TMD, the short external domains (ED) and longer cytoplasmic domains (CD), with cytoplasmic TMD-adjacent basic residues colored in red. B) Western blot of the crude extracts of N. benthamiana leaves agroinfiltrated with either a p33-expressing (p33) or an empty vector (EV) construct carried out with an anti-p33 primary antibody. The p33 loaded lane displayed protein bands, which correspond to the expected sizes of p33 monomers, dimers, and tetramers. Ponceau S staining was used to display the amount of loaded protein in the p33 and EV lanes. M: Molecular marker. C) AlphaFold3 prediction of the tetrameric p33 TMD with the two amino acids on the preceding CD and succeeding ED domains. The blue color of the helices indicates a confident pIDDT score for the p33 TMD and the PAE heatmap displays the confidence of the position of the four p33 TMD monomers with respect to each other in the model. D) AlphaFold3 predicted aligned error for the residues at the binding interface between the p33 TMD monomers.